Analisis Kepuasan dan Preferensi Pengguna terhadap Moda Angkutan Umum dan Transportasi Online di Rantepao, Kabupaten Toraja Utara - Sombolinggi, Azril Tangke; Bua', Rilva Toding; Dendo, Ermitha Ambun Rombe; Arrang, Abdias Tande (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2026)
Rantepao, as the capital of North Toraja Regency, experiences high social and economic activities that require an effective transportation system to support daily mobility. This study aims to analyze user satisfaction and preference toward online transportation and public transport in Rantepao. Data were collected through a questionnaire survey involving 200 respondents, consisting of 100 online transportation users and 100 public transport users. The analyzed variables include safety, service availability, fare, and service quality. Data analysis was conducted using multiple linear regression to examine factors influencing user satisfaction and binary logistic regression to analyze mode choice preference. The results indicate that user satisfaction with public transport is significantly influenced by fare, while satisfaction with online transportation is influenced by service availability, fare, and service quality. The binary logistic regression results show that service availability and safety increase the likelihood of choosing online transportation, whereas fare tends to encourage the selection of public transport. These findings highlight the importance of service characteristics in shaping transportation satisfaction and mode preference in Rantepao.